Escherichia Coli as a Biological Model for Reduction of Graphene Oxide (Indian Journal of Public Health Research & Development, 2020)
The present study was conducted to investigate the ability of bacteria to reduce Graphene Oxide (GO)sheets. Out of 82 bacterial isolates screened, one isolate was selected as a biological model for biosynthesisof reduced graphene oxide (RGO) nanosheets. This isolate was identified by morphological, biochemicaltests, VITEK2 System, and 16S rRNA gene sequencing, aligned and submitted to the NCBI, and confirmedas Escherichia coli strain E-NO.7 (accession no. MK685205). The UV-vis. absorption peak was around284 nm. The SEM images revealed thin, wrinkled, closely associated nanosheets. The weight percentage ofcarbon was 82.00% and oxygen was 18.00%. XRD analysis exhibited a broad diffraction peak at 2?= 26.5°corresponding to the interlayer spacing of 0.34 nm. The FTIR spectrum showed decrease in peaks associatedto oxygen functional groups, while other peaks vanished completely.
Keywords: Escherichia coli, Bacterial reduction of Graphene Oxide, Nanobiotechnology